Relationship among islamic dress, religious values and altruistic behavior - Khanam, Mahfuza (Dhaka University Journal of Biological Sciences, 2021)
The present study explored the relationship among Islamic dress, religious values and altruistic behavior. For the study, a total of 120 individuals (60 males and 60 females) were taken by purposive and convenient sampling method. The age of the participants was ranged from 18 to 26 years. To measure altruistic behavior, a pile of loose papers, some books, eraser, etc. and to measure the religious values of the participants, the Allport-Vernon-Lidzey Value Scale were applied on participants selected from different categories. Results showed that dress is significantly correlated with religious values and altruistic behavior. Significant differences have been found in both religious values and altruistic behavior between the participants wearing secular dress and Islamic dress and between male and female respondents. Significant interaction effect also has been found between dress and gender. Result revealed that the participants wearing Islamic dress have more religious values (M =37.31, SD = 6.89) and they show greater altruistic behavior (M = 5.48, SD =1.64) than those wear Secular dress (M =34.41, SD = 6.64 and M = 4.15, SD = 1.54) respectively. In terms of gender difference, it has been found that boys reported significantly less religious values (t = -2.14, p < .01) and greater altruistic behavior (t = 4.59, p <0.05) in comparison to girls. Dhaka Univ. J. Biol. Sci. 30(1): 13-21, 2021 (January)